Genomic and Epigenetic Advances in Focal Cortical Dysplasia Types I and II: A Scoping Review - Jesus-Ribeiro, Joana; Pires, Luís Miguel; Melo, João Daniel; Ribeiro, Ilda Patrícia; Rebelo, Olinda; Sales, Francisco; Freire, António; Melo, Joana Barbosa (Frontiers in Neuroscience, 2021)
Introduction: Focal cortical dysplasias (FCDs) are a group of malformations of cortical development that constitute a common cause of drug-resistant epilepsy, often subjected to neurosurgery, with a suboptimal long-term outcome. The past few years have witnessed a dramatic leap in our understanding of the molecular basis of FCD. This study aimed to provide an updated review on the genomic and epigenetic advances underlying FCD etiology, to understand a genotype-phenotype correlation and identify priorities to lead future translational research. Methods: A scoping review of the literature was conducted, according to previously described methods. A comprehensive search strategy was applied in PubMed, Embase and Web of Science from inception to 07-May-2020. References were screened based on title and abstract and posteriorly full-text articles were assessed for inclusion according to eligibility criteria. Studies with novel gene variants or epigenetic regulatory mechanisms in patients that underwent epilepsy surgery, with histopathological diagnosis of FCD type I or II according to Palmini’s or ILAE classification system, were included. Data were extracted and summarized for an overview of evidence. Results: Of 1156 candidate papers, 39 met study criteria and were included in this review. The advent of next generation sequencing enabled the detection in resected FCD tissue of low-level brain somatic mutations, that occurred during embryonic corticogenesis. mTOR signaling pathway, involved in neuronal growth and migration, is the key player in the pathogenesis of FCD II. Somatic gain-of-function variants in MTOR and its activators as well as germline, somatic and second-hit mosaic loss-of-function variants in its related repressors have been reported. However, the genetic background of FCD type I remains elusive, with a pleomorphic repertoire of genes affected. DNA methylation and microRNAs were the two epigenetic mechanisms that proved to have a functional role in FCD and may represent molecular biomarkers. Conclusion: Further research into the possible pathogenic causes of both FCD subtypes is required, incorporating single-cell DNA/RNA sequencing as well as methylome and proteomic analysis. The collected data call for an integrated clinicopathologic and molecular genetic diagnosis in current practice not only to improve diagnostic accuracy but also to guide the development of future targeted treatments.